Availability of Breast Milk for Preterm Neonates by Gestational Age during NICU Stay - Panda, Santosh Kumar; Sahoo, Kalpita; Jena, Pratap Kumar; Dhanawat, Avantika (Journal of Child Science, 2021)
The objective of this study was to explore the availability of expressed breast milk (EBM) volume for the premature neonates born from mothers in different gestational age groups during neonatal intensive care unit (NICU) stay. All preterm infants (extreme-preterm infant [EPTI, <28 weeks], very-preterm infant [VPTI, 28–316/7 weeks], and moderate-preterm infant [MPTI, 32–336/7 weeks]) and their mothers were included in the study. Infants not receiving mother's own milk and neonates deceased or discharged against medical advice, and the mother with illness during postpartum period were excluded from the study. A predesigned tool was used to collect information on maternal characteristics, neonatal characteristics, and milk diary for preterm neonates from the NICU case records. The primary outcome variable EBM volume available on day 7 was compared across three gestational groups. Logistic regression was used to predict EBM availability. A total of 78 preterm neonates, including 10 EPTI, 37 VPTI, and 31 MPTI, had average birth weight of 962.5 ± 228.25, 1,185.1 ± 183.14, and 1,293.2 ± 182.92 g, respectively. Receipt of exclusive breast milk among EPTI, VPTI, and MPTI was 80, 94, and 83.8%, respectively. Maternal characteristics were similar except for the mode of conception (p = 0.001), mode of delivery (p = 0.04), and antenatal steroid exposure (p = 0.02) among three gestational categories. The median (Q1–Q3) volume of EBM on day 7 were 160 (136.3–202.5), 150 (140–187.5), and 160 (150–220) mL for EPTI, VPTI, and MPTI neonates, respectively, without any statistical significance. Regression analysis suggests no effect of gestational age on EBM availability. The feasibility of mother's own milk use for extremely preterm neonates is similar to higher gestational preterm neonates.
Keywords: neonate; preterm birth; nutrition; human milk